Developing Android-based Application for Vocational High School Students in Learning Tense - Indri Nilam Atika; Marzul Hidayat; Fortunasari (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2024)
The students at one of Vocational High Schools in Sarolangun, Jambi, have some difficulties understanding the English Tense which is very essential in understanding sentence meaning related with time activities. This research aimed to develop an android-based application to help them overcome their difficulties. The development of the application made use of the Kodular website. The research method used was Research and Development (R&D) which followed the five stages of the ADDIE model as the developmental procedure. The stages of the ADDIE model in accordance with Branch theory are 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data related with developmental process were collected using questionnaire then analyzed quantitatively and qualitatively. The result of this research was in form of an android-based application called FunTense which accommodates students’ needs and preferences in the learning English Tense. The result indicated that the development was valid proved by the result of media validation with 78% score percentage and content validation with 91% score percentage. Further, the students response indicated as excellent with total score percentage 92,95%. It can be concluded that the FunTense application developed in this research was valid and can be used as a learning media.